Risk‐adjusted hospital mortality rates for stroke: evidence from the Australian Stroke Clinical Registry (AuSCR). Issue 8 (1st May 2017) - Cadilhac, Dominique A; Kilkenny, Monique F; Levi, Christopher R; Lannin, Natasha A; Thrift, Amanda G; Kim, Joosup; Grabsch, Brenda; Churilov, Leonid; Dewey, Helen M; Hill, Kelvin; Faux, Steven G; Grimley, Rohan; et al.
Abstract: Objectives: Hospital data used to assess regional variability in disease management and outcomes, including mortality, lack information on disease severity. We describe variance between hospitals in 30‐day risk‐adjusted mortality rates (RAMRs) for stroke, comparing models that include or exclude stroke severity as a covariate. Design: Cohort design linking Australian Stroke Clinical Registry data with national death registrations. Multivariable models using recommended statistical methods for calculating 30‐day RAMRs for hospitals, adjusted for demographic factors, ability to walk on admission, stroke type, and stroke recurrence. Setting: Australian hospitals providing at least 200 episodes of acute stroke care, 2009–2014. Main outcome measures: Hospital RAMRs estimated by different models. Changes in hospital rank order and funnel plots were used to explore variation in hospital‐specific 30‐day RAMRs; that is, RAMRs more than three standard deviations from the mean. Results: In the 28 hospitals reporting at least 200 episodes of care, there were 16 218 episodes (15 951 patients; median age, 77 years; women, 46%; ischaemic strokes, 79%). RAMRs from models not including stroke severity as a variable ranged between 8% and 20%; RAMRs from models with the best fit, which included ability to walk and stroke recurrence as variables, ranged between 9% and 21%. The rank order of hospitals changed according to the covariates included in the models, particularly for those hospitals with the highest RAMRs. Funnel plots identified significant deviation from the mean overall RAMR for two hospitals, including one with borderline excess mortality. Conclusions: Hospital stroke mortality rates and hospital performance ranking may vary widely according to the covariates included in the statistical analysis.